2014
DOI: 10.1128/jvi.00618-14
|View full text |Cite
|
Sign up to set email alerts
|

Duplication of the A17L Locus of Vaccinia Virus Provides an Alternate Route to Rifampin Resistance

Abstract: Specific gene duplications can enable double-stranded DNA viruses to adapt rapidly to environmental pressures despite the low mutation rate of their high-fidelity DNA polymerases. We report on the rapid positive selection of a novel vaccinia virus genomic duplication mutant in the presence of the assembly inhibitor rifampin. Until now, all known rifampin-resistant vaccinia virus isolates have contained missense mutations in the D13L gene, which encodes a capsid-like scaffold protein required for stabilizing me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 39 publications
(71 reference statements)
3
32
0
Order By: Relevance
“…D13 has no transmembrane domain and associates with the viral membrane through interaction with the N-terminus of A17 (Bisht et al, 2009; Unger et al, 2013). This interaction is supported by a recent finding that duplication or over expression of A17 confers resistance to rifampicin (Erlandson et al, 2014). The removal of D13 trimers during the transition from IV to MV is associated with processing of A17 (Bisht et al, 2009).…”
Section: Rifampicin and The D13 Scaffold Proteinmentioning
confidence: 53%
“…D13 has no transmembrane domain and associates with the viral membrane through interaction with the N-terminus of A17 (Bisht et al, 2009; Unger et al, 2013). This interaction is supported by a recent finding that duplication or over expression of A17 confers resistance to rifampicin (Erlandson et al, 2014). The removal of D13 trimers during the transition from IV to MV is associated with processing of A17 (Bisht et al, 2009).…”
Section: Rifampicin and The D13 Scaffold Proteinmentioning
confidence: 53%
“…Interestingly, two of the seven breakpoints identified in this study were identical to those observed in virus populations passaged in HeLa cells (14), suggesting the presence of these variants at a level below the limit of detection in the ΔE3L parent virus or indicating that these are preferential sites for recombination. These results, combined with studies demonstrating CNV in other poxvirus genes in response to selective pressure (24)(25)(26), continue to reveal CNV as a mechanism for rapid adaptation of VACV. a The ORF containing the mutation is shown for variant alleles (bold) not present in the ΔE3L parent virus (also see Fig.…”
Section: Resultsmentioning
confidence: 82%
“…The observation of gene amplification after only a few passages in several independent experiments (15,21,22) suggests that gene amplification may be a frequent occurrence during VACV replication. Our deep-sequencing data revealed rare instances of a specific J2R-L5R breakpoint in PRO1190-adapted viruses that have only a single copy of rhtrs1 ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The pool of potential new pathogens is large, so defining biomolecular signatures that may be predictive of agents poised to cross into new species could improve our ability to anticipate and avert epidemics. Gene amplification may be one such marker of imminent adaptation: it is a broad evolutionary mechanism that has been described across all domains of life, including viruses (15,(20)(21)(22)40). In general, gene amplification provides two potential benefits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation